Community-acquired neonatal SARS-CoV-2 infection: case report - Mohammad Kamal Mansour, Kamila (2024)
Background and Objectives: Data collection on the incidence of COVID-19 is conducted less frequently in newborns (NB) than in adults. In view of the small number of described neonatal SARS-CoV-2 infections, in this study, we report a clinical case of community-acquired COVID-19 infection in a newborn. Methods: Clinical characteristics were collected from the medical records from April 2021 until the final outcome of the newborn in May 2021. Results: This article discusses the case of a full-term male newborn aged 38 weeks. On the 17th day of life, this newborn was admitted to the pediatric unit with fever and zone 4 jaundice, mild lower chest retraction and tachypnea. The mother was diagnosed with COVID-19. Late neonatal sepsis with pulmonary focus was detected. The newborn was hospitalized and the antigen test for COVID-19 came back positive. The condition of the neonate rapidly deteriorated and he was referred to the neonatal intensive care unit (NICU), where he was intubated and placed on pressure-controlled mechanical ventilation. During his second week in the NICU, he developed severe pulmonary hypertension with decreased peripheral oxygen saturation and tachycardia. The newborn required blood transfusion and was put into prone position during part of the treatment. Reductions in mechanical ventilation parameters were not tolerated by the NB’s organism and he developed progressive hypoxemia. The newborn died 1 month and 3 days after hospitalization. Conclusion: Our study shows a case of community-acquired COVID-19 that progressed to the severe form of the disease.